Model Pembelajaran Problem Based Learning: Sebuah Model Pembelajaran Yang Dapat Meningkatkan Keterampilan Berpikir Kreatif Peserta Didik pada Materi Metabolisme - Ainun Azizah; Idad Suhada; Epa Paujiah (Edu Berkah Khatulistiwa, 2023)
The Problem Based Learning learning model is considered suitable to be applied to the teaching of metabolism material, because the learning process includes the cognitive and affective domains of students so that they can achieve creative thinking processes. The purpose of this study is to find out the increase in students' creative thinking in class XII SMA-X metabolism material through the application of the Problem Based Learning (PBL) learning model assisted by e-LKPD learning media. This study used a quantitative approach and the research method used was experimental research with a quasi-experimental design. The results of the study show that the application of the Problem Based Learning learning model can improve creative thinking skills. This is evidenced by the acquisition of N-Gain scores in classes that use the Problem Based Learning learning model assisted by e-LKPD learning media of 0.64 in the medium category. The N-gain value was obtained from the analysis of students' pretest and posttest scores. The use of the Problem Based Learning learning model assisted by e-LKPD learning media has an effect on students' critical thinking skills. The increase in the results of students' test scores proves that the Problem Based Learning learning model is useful for improving students' creative thinking skills in metabolic material.